ANALISIS PEMBENTUKAN DISIPLIN PADA PENGURUS ORGANISASI SISWA INTRA SEKOLAH (OSIS) SMP NEGERI 2 PONTIANAK - Tamam, Badrot; Wicaksono, Luhur; Yuline, Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the factors forming discipline in the management of intra-school student organizations in SMP Negeri 2 Pontianak. The method used by using qualitative research approach method. The subjects of this study were 10 student council administrators and guidance and counseling teachers at Pontianak 2 Public Middle School. Data collection techniques used are direct observation techniques of direct communication and observation of data collection tools with observation guidelines and interview guidelines. While the data analysis technique uses formulas and domain analysis.The results of the findings based on observational and interview data of this study were analyzed and concluded that the factors forming the discipline of the management board of the SMP Negeri 2 Pontianak were: 1) Dominant Factors namely self-awareness in good categories, while those that must be considered in the formation of the discipline of the public junior high school student council 2 Pontianak is 2) Other Factors namely Examples with very poor categories. Based on table 4.1, the results of interviews and observations on the average formation of discipline in the board of directors of the SMP Negeri 2 Pontianak are 2.45 which are categorized sufficient.Â Keywords: formation of discipline, student council administrators